Common and Rare Genetic Risk Factors Converge in Protein Interaction Networks Underlying Schizophrenia - Chang, Xiao; Lima, Leandro de Araujo; Liu, Yichuan; Li, Jin; Li, Qingqin; Sleiman, Patrick M. A.; Hakonarson, Hakon (Frontiers in Genetics, 2018)
Hundreds of genomic loci have been identified with the recent advances of schizophrenia researches in genome-wide association studies (GWAS) and sequencing studies. However, the functional interactions among those genes remain largely unknown. We developed a network-based approach to integrate multiple genetic risk factors, which lead to the discovery of new susceptibility genes and casual sub-networks or pathways in schizophrenia. We identified significantly and consistently over-represented pathways in the largeest schizophrenia GWA studies, which are highly relevant to synaptic plasticity, neural development and signaling transduction, such as long-term potentiation, neurotrophin signaling pathway and the ERBB signaling pathway. We also demonstrated that genes targeted by common SNPs are more likely to interact with genes harboring de novo mutations (DNMs) in the protein-protein interaction (PPI) network, suggesting a mutual interplay of both common and rare genetic variants in schizophrenia. We further developed an edge-based search algorithm to identify the top-ranked gene modules associated with schizophrenia risk. Our results suggest that the N-methyl-D-aspartate receptor (NMDAR) interactome may play a leading role in the pathology of schizophrenia, as it is highly targeted by multiple types of genetic risk factors.